INSIDER TRADING IN CAPITAL MARKET (KAJIAN LITERATUR EMPIRIS AKUNTANSI BERBASIS PASAR MODAL) - Amelia, Yunia (Jurnal Bisnis Darmajaya, 2016)
This article presents literature study based on the capital market that is derived from various sources of books, study the papers from 10 international journals that published between the years 1997-2012, identify gaps on the existing literature and indicate the future research for researchers. This article provides the study of the literature with comprehensive and makes a critical analysis of the insider trading in the stock market. This research is expected to be a source of information that is very useful for researchers and managers who want to understand the insider trading and do further research on diversities and interesting issue about this problem.Keywords : insider tranding, capital market